Translation as a Transaction Cost - Pym, Anthony (Meta, 1995)
AbstractThe author develops a translation theory which considers source and target elements as social actors engaged in communication in order to achieve mutual benefits. The model suggests, among other things, that the social effort put into communication should not exceed the mutual benefit ensuing from the interaction. Applied to translation, the aim of the model is to formulate general hypotheses about the context in which translation should occur and the social costs it should involve.